Hyperpolarized 13 C‐MRS can Quantify Lactate Production and Oxidative PDH Flux in Murine Skeletal Muscle During Exercise - Curtis, M. Kate; McGing, Jordan J.; Stubbs, Brianna J.; Ball, Vicky; Cochlin, Lowri E.; O'Neill, David P.; Laustsen, Christoffer; Cole, Mark A.; Robbins, Peter A.; Tyler, Damian J.; Miller, Jack J. (NMR in biomedicine, 2025)
Existing techniques for the non‐invasive in vivo study of dynamic changes in skeletal muscle metabolism are subject to several limitations, for example, poor signal‐to‐noise ratios which result in long scan times and low temporal resolution. Hyperpolarized [1‐ 13 C]pyruvate magnetic resonance spectroscopy (HP‐MRS) allows the real‐time visualization of in vivo metabolic processes and has been used extensively to study cardiac metabolism, but has not resolved oxidative phosphorylation in contracting skeletal muscle. Combining HP‐MRS with an in vivo muscle hindlimb electrical stimulation protocol that modelled voluntary exercise to exhaustion allows the simultaneous real‐time assessment of both metabolism and function. The aim of this work was to validate the sensitivity of the method by assessing pyruvate dehydrogenase (PDH) flux in resting vs. working muscle: measuring the production of bicarbonate (H 13 CO 3 − ), a byproduct of the PDH‐catalysed conversion of [1‐ 13 C]pyruvate to acetyl‐CoA. Mice ( n = 6) underwent two hyperpolarized [1‐ 13 C]pyruvate injections with 13 C MR spectra obtained from the gastrocnemius muscle to measure conversion of pyruvate to lactate and bicarbonate, one before the stimulation protocol with the muscle in a resting state and one during the stimulation protocol. The muscle force generated during stimulation was also measured, and 13 C MRS undertaken at a point of ~50% fatigue. We observed an increase in the bicarbonate/pyruvate ratio by a factor of ~1.5×, in the lactate/pyruvate ratio of ~2.7×, together with an increase in total carbon (~1.5×) that we attribute to perfusion. This demonstrates profound differences in metabolism between the resting and exercising states. These data therefore serve as preliminary evidence that hyperpolarized 13 C MRS is an effective in vivo probe of PDH flux in exercising skeletal muscle and could be used in future studies to examine changes in muscle metabolism in states of disease and altered nutrition.